Correlation between leg length discrepancy and asymptomatic sacroiliac joint dysfunction in young males - Wiangkham, Taweewat; Rinrit, Pattamaporn; Choprateep, Mananya; Thamrongthanakul, Ralita; Chidnok, Weerapong (Chulalongkorn Medical Journal, 2022)
Background: Sacroiliac joint dysfunction (SJD) is an important cause of low back pain (LBP), commonly overlooked. Although the association of leg length discrepancy (LLD) and LBP was established, no study has examined the association between LLD and asymptomatic SJD (ASJD). Objective: To examine the correlation between LLD and ASJD in young males. Methods: One hundred subjects wearing a comfortable and thin uniform were randomized into three rooms (consisting of leg length measurement, palpation and special test rooms). One high valid and reliable assessor was allocated in each room. All subjects were assessed three times (one time a room and then randomly assigned by a project manager to other rooms until reaching three times a test) to reduce potential biases and errors. Logistic regression was used to examine the association between the degree of LLD and ASJD. The association between ASJD and affected leg was examined by Chi-square test. Results: The mean age and LLD of subjects were 20.3 1.4 years and 6.3 3.8 mm., respectively. The number of structural and functional LLD were found (50 subjects each type). The ASJD was found in 95 (46 structural, 49 functional) subjects. There was no significant correlation between the degree of LLD and ASJD (odds ratio = 0.99 (95% confident interval (0.78, 1.26), P = 0.94). However, the affected leg (short leg) associated with ASJD (P < 0.001). Conclusions: Young males with mild LLD can have ASJD. The study suggests that the shorter leg in people with mild LLD could have higher chance for ASJD. Shoe lifts may be an optional procedure to prevent symptomatic SJD, especially structural LLD.